Community centers in Singapore - Seah, Chee-Meow (1980)
Community centers were primarily designed to promote grassroot participation in Singapore. Through time their role has expanded to include information dissemination, all done to promote the idea of nation-building, development, and communal harmony. In July 1960, the Singapore government formed a statutory board known as the People's Association to establish control over some two dozen existing community centers in the place. The Association organized varied types of activities for the centers like recreational, vocational, cultural, educational, etc. The centers' main conviction is to involve the people not only as mere participants but also as shapers of the centers. Management committees whose membership is open to every adult citizen were thus formed to assist in the centers' operation. Evaluating the success of the centers may be difficult since promoting nation-building and communal harmony is not done by them solely. But one has only to see through the extent of involvement of the people themselves with the center, the fact that poorer citizens are served just as well and the actualization of popular involvement at grassroots level, to adjudge these community centers as successes.
Keywords: Community development; Community centers -- Singapore; Recreational facilities -- Singapore